Health, equity, and human rights : perspectives and issues - Prakasam,CP,Ed (Indian Association for Social Sciences and Health ; Serials Publications, 2010)
Papers presented at the Sixth National Conference of Indian Association for Social Sciences and Health, held at Pondicherry University, during 7-8 March 2009.